Some interesting plants of the Coto Nacional de las sierras de Cazorla y Segura (Jaén) - Martínez Parras, José María; Peinado Lorca, Manuel (Lazaroa, 2014)
Thirty taxa of chorological interest collected in Cazorla y Segura (Jaén, Spain) are cited.